Про дефект нещільності неперервних вкладень у шкалі гільбертових просторів - Божок, Р.В. (Український математичний журнал, 2008)
Установлена формула для определения дефекта при непрерывном вложении подпространств в шкале гильбертовых пространств. The formula is obtained for the determination of a defect under the continuous imbedding of subspaces in the scale of Hilbert spaces.